Perception: themes in literature - Carlsen, G. Robert; Carlsen, Ruth Christoffer (New York : Webster Division, McGraw-Hill, 1975)
A thematically arranged anthology of poems, short stories, plays, and novellas for the eighth-grade reader.
Includes index.
Keywords: Literature, Modern; Literature -- Collections